Disappearing green: Shrubs decline and bryophytes increase with nine years of increased snow accumulation in the High Arctic. (22nd September 2019) - Cooper, Elisabeth J.; Little, Chelsea J.; Pilsbacher, Anna K.; Mörsdorf, Martin A.
Abstract: Question: How does increased snow depth affect plant community composition of High Arctic tundra, and can the Normalized Differential Vegetation Index (NDVI) detect induced changes? Location: Adventdalen, Spitsbergen, Svalbard (78°10′ N, 16°04′ E). Methods: We manipulated snow depth on the tundra using fences, resulting in Deep, Medium, and Ambient snow regimes. Increased snow led to warmer winter soil temperatures, a delayed onset of growing season and wetter conditions during the early growing season. Plant community composition of living and dead plant material was recorded after nine years. NDVI was measured at the plot level using a handheld sensor. Results: Community composition and the abundance of typically dominant shrub species were substantially different in the Deep compared to the Ambient regime. Deep had lower cover of live shrubs ( Cassiope tetragona, Dryas octopetala and Salix polaris ) and Luzula confusa, and higher cover of dead shrubs ( Cassiope and Dryas ) compared to the other snow regimes. Bryophyte cover was highest in Medium . NDVI was positively correlated to the cover of living vascular plants and negatively correlated to cover of dead vascular plants. Accordingly, Deep snow regime had reduced NDVI, reflecting the contribution of dead Cassiope and Dryas . Conclusion: Snow regime strongly influenced community composition in High Arctic plant communities. Enhanced snow regimes had more dead shrubs, reduced Luzula and increased bryophyte cover than ambient conditions. These differences were detectable by handheld NDVI sensors. Abstract : We used snowfences to enhance snow depth and duration of snow lie for nine years in Svalbard. We observed differences in plant community composition between snow treatments that were also detectable by a handheld Normalized Differential Vegetation Index sensor. The deepest snow regime had the lowest cover of live shrubs and Luzula confusa, and moderately enhanced snow promoted bryophyte cover.